Effect of Dendrobium officinale Extraction on Gastric Carcinogenesis in Rats - Zhao, Yi (Evid Based Complement Alternat Med, 2016)
Dendrobium officinale (Tie Pi Shi Hu in Chinese) has been widely used to treat different diseases in China. Anticancer effect is one of the important effects of Dendrobium officinale. However, the molecular mechanism of its anticancer effect remains unclear. In the present study, gastric carcinogenesis in rats was used to evaluate the effect of Dendrobium officinale on cancer, and its pharmacological mechanism was explored. Dendrobium officinale extracts (4.8 and 2.4 g/kg) were orally administered to the rats of the gastric carcinogenesis model. Compared with the cancer model group, the high dose of Dendrobium officinale extracts significantly inhibited the rate of carcinogenesis. Further analysis revealed that Dendrobium officinale extracts could regulate the DNA damage, oxidative stress, and cytokines related with carcinogenesis and induce cell apoptosis in order to prevent gastric cancer.